PENGARUH PENAMBAHAN SOLUTION PREHEATER TERHADAP LAJU PRODUKSI UAP REFRIGERAN PADA GENERATOR MESIN REFRIGERASI SIKLUS ABSORPSI - Demak, Reyhan Kiay (Jurnal MEKANIKAL, 2014)
Abstract: The effect of Addictive Solution Preheater on Refrigerant Vapor Production Rate of Absorption Cycle on Refrigerant Generator Engine The purpose of this study was to determine the effect of solution preheater absorption cycle that utilizes two springs with different temperatures on the rate of production of the refrigerant vapor in the generator. In this research, testing by simulating the use of two springs with different temperature, high temperature generator is used to heat and temperature is used to heat a heat exchanger (preheater solution) that will heat up the rich solution before entering the generator. The test results showed an increase in the flow rate of refrigerant which is produced by generator with temperature hot water that goes into solution preheater, the temperature of the hot water entering the generator temperature variation of 80° C and hot water preheater from 55 till 70oC entry solution obtained an increase in refrigerant flow rate of 0.000381 kg/s solution without the use of a preheater and preheater with the use of solution increased to 0.000387 kg/s at temperatures up to 55oC maximum performance of 0.0005 kg/s temperature of 70oC. Keywords: Refrigeration machine, absorption cycle, H20-LiBr, solution preheater, the refrigerant vapor.